Driving Factors of Students’ Achievement: A Case Study of A Private University in Zhanjiang, China - Qin, Yueming (Scholar: Human Sciences, 2025)
Purpose: This study explores the factors that affect students’ achievement in private universities in China. This study investigated the impact of four independent variables (teacher commitment, emotional intelligence, professional development, and professional community) on the dependent variable (student achievement). Research Design, Data, and Methodology: The validity and reliability of the survey questionnaire were tested using the Index of Item-Objective Congruence (IOC) and Cronbach Alpha (n=30). Multiple linear regression analysis was used to analyze the effective survey questionnaire data of 70 teachers from Zhanjiang University of Science and Technology to verify the relationship between independent and dependent variables. Then, a 14-week IDI intervention was conducted on 30 teachers, and paired sample t-tests were conducted on data before and after the IDI to verify the impact of IDI on variables. Results: The results of multiple linear regression analysis indicate that teacher commitment, emotional intelligence, professional development, and professional community have a significant impact on student achievement. The paired sample t-test results indicate that teacher commitment, emotional intelligence, professional development, and professional community have significantly improved after IDI, and student achievement has also significantly improved after IDI. Conclusions: Teacher commitment, emotional intelligence, professional development, and professional community can affect the student’s achievement at Chinese private universities. Student achievement can be enhanced by enhancing teacher commitment, emotional intelligence, professional development, and professional community.